Nazis after Hitler : how perpetrators of the Holocaust cheated justice and truth - McKale, Donald M. 1943- (Rowman & Littlefield, 2014)
This deeply researched and informative book traces the biographies of thirty typical perpetrators of the Holocaust who survived World War II. The author reveals that the perpetrators were only rarely tried or punished for their crimes, and nearly all alleged their innocence in Germany's extermination of nearly six million European Jews during the war. He highlights the bitter contrasts between the comfortable postwar lives of many war criminals and the enduring suffering of their victims. The author shows how immediately after the war's end in 1945, Hitler's minions carried on what amounted to a massive postwar ideological campaign against Jews. The perpetrators helped advance Holocaust denial without having denied the Holocaust happened. Written in a compelling narrative style, this is the first book to provide an overview of the lives of Nazis who survived the war, the vast majority of whom escaped justice.